Public procurement and competitiveness of women-owned businesses: a structural equation model (SEM) for genderresponsive procurement in Uganda - Nagitta Oluka, Pross; Okoche, Michael; Mugurusi, Godfrey (World Journal of Entrepreneurship, Management and Sustainable Development, 2020)
Several intergovernmental organizations claim that the involvement of women in public procurement has a direct impact on sustainable development and growth, especially in the developing world, yet we know very little of such claim. This study aims to empirically examine how public procurement can contribute to women empowerment by boosting the competitiveness of women-owned businesses (WOBs) in Uganda. Design/methodology/approach – In this study, a cross-sectional survey method is used. Quantitative data were gathered from a sample of 371 respondents in Ministries, Departments and Agencies (MDAs) and a section of women entrepreneurs in Uganda’s capital Kampala. From the literature review, six hypotheses were formulated and tested using structural equation modelling (SEM). A research model is developed and presented. Findings – All hypotheses, except for one, were supported. Procurement policy had a significant influence on evaluation criteria, contract management and most importantly, on the competitiveness of WOBs. Within the procurement process, evaluation criteria had a significant influence on the competitiveness of WOBs, while the influence of contract management on competitiveness of WOBs was not statistically significant. We, therefore, concluded that public procurement can indeed enhance women empowerment through a gender-responsive procurement policy. Above all, pre-contract award interventions such as streamlining evaluation criteria to ease access ofWOBsto public procurement contracts seem have the most significant impact to competitiveness of WOBs compared to post-ward interventions during contract management. Originality/value – This study offers a research-based model that articulates the role of procurement policy as an enabler for competitiveness of WOBs in developing countries. The model proposes a combination of both policy (a direct influence) and interventions in the supplier selection process (an indirect influence) to boost the competitiveness of WOBs.
Keywords: Public procurement; Developing countries; Supplier evaluation; Women empowerment; Procurement policy; Gender responsive procurement